Water relations of melon (Cucumis melo) plants in soilless culture - Ismail, Mohd Razi; Muhammad, Fauzi (Universiti Putra Malaysia Press, 1995)
Melon (Cucumis melo) plants were grown in a peat and sand mixture under water availability of 25, 50, 166% and field capacity. The respective amount of water added to substrate was 300, 600, 2000 and 1200 ml per day. Vegetative growth and yield decreased proportionately according to water availability. Overwatering above substrate field capacity resulted in the highest growth and yield as the plants compensated for the influence of high evaporative demand in the microclimate. Total soluble solids in the fruit increased rapidly during fruit development under reduced water availability. Increased water availability improved leaf water status, stomatal response and photosynthesis rate. At lowest water availability, a reduction in leaf water status caused photosynthesis rate to decline and to reach negative values by the end of the growth period. A relationship between leaf water status and stomatal resistance was established and is discussed with reference to hydraulic and nonhydraulic causes controlling stomatal responses.